The genome sequence of the Elephant Hawk-moth, Deilephila elpenor (Linnaeus, 1758) [version 1; peer review: 2 approved] - Douglas Boyes; Peter W.H. Holland (Wellcome Open Research, 2024)
We present a genome assembly from an individual female Deilephila elpenor (the Elephant Hawk-moth; Arthropoda; Insecta; Lepidoptera; Sphingidae). The genome sequence is 414.1 megabases in span. Most of the assembly is scaffolded into 30 chromosomal pseudomolecules, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 15.37 kilobases in length. Gene annotation of this assembly on Ensembl identified 11,748 protein coding genes.